2019
DOI: 10.1123/japa.2017-0410
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Interventions for Physical Activity, Sedentary Behavior, and Sleep in Adults Aged 50 Years and Older: A Systematic Literature Review

Abstract: We provide a systematic review of interventions utilizing mobile technology to alter physical activity, sedentary behavior, and sleep among adults aged 50 years and older. A systematic search identified 52 relevant articles (randomized control trial [RCT], quasi-experimental, pre/post single-group design). Of 50 trials assessing physical activity, 17 out of 29 RCTs and 13 out of 21 trials assessed for pre/post changes only supported the effectiveness of mobile interventions to improve physical activity, and 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 88 publications
1
61
0
2
Order By: Relevance
“…Persuasive technology is a branch of mHealth in which the aim is to use digital technology to guide users to change their attitudes and behavior by enhancing the effects of behavioral change techniques [ 24 ]. mHealth interventions show promise in encouraging older people to increase their levels of physical activity as reported in systematic reviews [ 25 - 28 ]. Because there is a lack of properly designed trials in this area, none of these systematic reviews drew conclusions on whether the mHealth is more effective or can enhance the effect of the conventional intervention to promote physical activity in older people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persuasive technology is a branch of mHealth in which the aim is to use digital technology to guide users to change their attitudes and behavior by enhancing the effects of behavioral change techniques [ 24 ]. mHealth interventions show promise in encouraging older people to increase their levels of physical activity as reported in systematic reviews [ 25 - 28 ]. Because there is a lack of properly designed trials in this area, none of these systematic reviews drew conclusions on whether the mHealth is more effective or can enhance the effect of the conventional intervention to promote physical activity in older people.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous trials, most of the mHealth interventions that were included in the reviews used only websites, DVDs, and texting instead of face-to-face physical activity training and health education [ 25 - 28 ]. Recently, studies have shown that the newly developed technologies, including wearable devices and social media, showed promising effects in promoting physical activity in many populations (eg, young people, cancer survivors) [ 33 - 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…E-health interventions have also been implemented among older people, and their effects on promoting physical activity have been evaluated in clinical trials. A few systematic reviews have shown that many of them employed different e-health strategies, and many individual trials have shown that many e-health interventions are effective at increasing physical activity but some are not [25,26]. The number of trials included in these reviewers was small and therefore the effects of e-health interventions were not concluded in these reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have considered publications in a short time span (e.g., [57]), while others have considered specific problem areas such as pain [58], cardiovascular disease [14], or balance and fall risk assessments [59]. In addition, some research has focused on interventions that use mobile technology to alter physical activity, sedentary behavior, and sleep in older adults [60]. The evidence collected in previous research is limited to technologies targeting a specific condition or promoting activities as contrast to the present work in which we focus on technology for health management in general.…”
Section: Discussionmentioning
confidence: 99%